Formation of the vertical stability of the body of junior schoolchildren with hearing impairments in the process of physical education - Afanasyev, Sergiy; Burdayev, Kirill (Journal of Education, Health and Sport, 2017)
Human activities are largely determined by the ability to effectively hold certain static dynamics. Rational movements and poses determine the result of human activity, and therefore the regulation of the posture of the human body has been the subject of research and experimentation for many decades and even centuries. Support for the vertical position of the body is one of the most important conditions of human life, which allows him to actively interact with the environment. Supporting the balance of the body in the main rack is an active, dynamic process involving many body systems. The question of formation of the vertical stability of the body of junior schoolchildren with hearing impairment is not sufficiently studied at the moment. Objectives of the study: to determine the peculiarities of the vertical stability of the body of children of junior school age with hearing impairment in the process of physical education. Research results. We evaluated the level of development of the static balance of the body of children with reduced hearing by using the Bondarevsky test. The studied indices of pupils of 7 and 10 years correspond to the average level of vertical stability of the body of children of elementary school age with reduced hearing in the sample of Bondarevsky. A particularly large number of such children, namely 81,3%, was found among 7 and 8 year old participants in the experiment, which needs special attention for younger pupils with hearing impairment of the specified age. Conclusions. Assessment of the studied indicators showed that children 7 and 10 years are characterized by average, and 8 and 9 years – low level of static stability of the body. The positive dynamics of the formation of vertical resistance of children aged 7 to 10 years with reduced hearing testifies to the adequacy of physical education devices used in special general educational institutions for children with hearing impairment, but the low parameters of the static balance of the examined body, obtained experimentally, indicate the need for additional measures, aimed at increasing the level of vertical stability of the body of the participants in the experiment.